ÉPOCAS DE APLICAÇÃO DE NITROGÊNIO E SEUS EFEITOS EM COMPONENTES DA PRODUÇÃO EM AVEIA - Viera, Rogério; Noronha, Uelinton; Martins, João A. K.; Valentini, Ana P. F.; Gaviraghi, Fernando; Santos, Cleverson D. d.; Berto, Jorge L.; Uhde, Leonir T.; Krüger, Cleusa A. M. B.; Silva, José A. G. d. (Salão do Conhecimento, 2013)
Resumo